The Evolution of "Association" as a Model for Lay/Religious Collaboration in Catholic Education, Part I: From "One and Only Masters" to the Lasallian Family, 1719-1986 - Tidd, O.S.B., Kevin M. (Catholic Education: A Journal of Inquiry and Practice, 2009)
Maintaining Catholic identity is a struggle that takes on many forms. For schools with historical ties to founding religious communities, this question often takes the form of how to preserve and grow the charisms of the religious community in the absence of any members of that community on the school faculty or staff. This article, first of a two-part series, explores how one community, the Brothers of the Christian Schools, came to answer that question.